Oral Health Care Practice and Circumstances during Covid-19 among Dental Patients in Tertiary Care Hospital in Nepal - Prajapati, D.; Hada, B.; Ghimire, G.; KC, S.; Singh, S.; Makaju, S.; Mahanta, S. K. (Kathmandu University Medical Journal, 2022)
Background Patients are hesitant to enter a dental hospital because of the significant danger of cross infection and illness transmission due to rapid spread of corona virus. Objective To assess knowledge regarding Covid-19, oral health practices and circumstances on dental treatment during a pandemic. Method Cross sectional study was conducted among patients visiting dental department of Dhulikhel hospital from September to October 2020. Questionnaires were interviewed following safety protocols regarding the pandemic and descriptive analysis was performed. Both verbal and written consent as well as ethical approval was taken before the study. Result A total 411 patients aged 14 to 75 years old from 14 different districts across Nepal participated in the study. All of the patient were free of Covid-19 symptoms and had strong knowledge and awareness about disease transmission. During the crisis 96% of the people maintain good oral hygiene while 25.8% acquire new dental problems where majority experienced oral discomfort and swelling, 93.2% of them did not attend a dental clinic or hospital in the interim owing to fear and inaccessibility. Majority of the participants were impressed by the safety precautions and preparations during treatment and 99.3% strongly suggest or pledge to visit dental department if necessary during the pandemic. Conclusion Dental patient visiting Dhulikhel hospital is highly aware of current health crisis, possible transmission and preventive measures. Proper safe hospital setup can encourage them to seek dental treatment during crisis. Dental pain and swelling in Endodontic department recorded most common dental emergency during this pandemic.